Plant functional diversity influences water and carbon fluxes and their use efficiencies in native and disturbed dryland ecosystems. Issue 5 (27th July 2022) - Castellanos, Alejandro E.; Hinojo‐Hinojo, César; Rodriguez, Julio C.; Romo‐Leon, Jose Raul; Wilcox, Bradford P.; Biederman, Joel A.; Peñuelas, Josep
Abstract: Vegetation is changing rapidly in dryland ecosystems, but critical gaps remain in understanding the long‐term fluxes of carbon (C) and water. We used 6 years of data from two adjacent eddy covariance sites in the Sonoran Desert, a species‐rich woody C3 native shrubland and a species‐poor C4 shrubland converted to buffelgrass savanna. Although emphasis has been given to the physical determinants of productivity in dryland ecosystems, we assessed how PFTs changes influenced (1) water and C fluxes and (2) water‐use (WUEe) and intrinsic C‐use efficiencies (CUE ei ) in the two sites under the same climatological conditions. We hypothesized that changes in PFTs would alter accessibility, rate and use efficiencies of water and carbon, with poorly known effects on the long‐term fluxes and efficiencies. Annual net ecosystem productivity (NEP) in the shrubland was a C‐source in drier years and a sink in others. However, longer C uptake, greater WUEe and lower CUE ei were the crucial drivers for higher and positive NEP (C sink) in the savanna. Annual and seasonal WUEe and CUE ei discrepancies indicated the importance of dominant PFTs after disturbance and ecohydrological feedbacks. As the world becomes drier and vegetation disturbance more common, the role of PFT changes should contribute to gaining a clearer understanding of their role in the C and water fluxes of dryland ecosystems.